EFEKTIFITAS VAKSINASI COVID-19 TERHADAP ANGKA KESAKITAN COVID-19 MAHASISWA DI AKFAR YAMASI ANGKATAN 2019 BULAN JULI TAHUN 2022 - Agust Dwi Djajanti (Jurnal Kesehatan Yamasi Makassar, 2022)
A research has been conducted with the title "Effectiveness of Covid-19 vaccination on the morbidity rate of Covid-19 students of AKFAR Yamasi Class of 2019 in July 2022. This type of research is an observational descriptive study with a quantitative approach and uses a questionnaire research instrument. Where the population used as respondents is 140 students of AKFAR Yamasi Class of 2019, while the number of samples obtained using the slovin formula is obtained by 15 respondents, then the morbidity rate (Risk Ratio) is calculated by comparing sick respondents (infected with covid-19) with respondents who are not sick (not infected with covid-19). Obtained a risk ratio of 26.7% while those who are not at risk of getting sick are 73.3%. Because the morbidity rate is <50%, the covid-19 vaccination is said to be effective